2022
DOI: 10.1109/tasc.2022.3187245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of AC-Superconducting Multiphase Symmetric-Winding Topologies for Wind Power Generators With PM Rotors

Abstract: In this paper, an AC superconducting multi-phase symmetric-winding machine is designed for a wind power generator to improve its performance and reduce losses, where four handpicked topological designs were explored and compared. In particular, it is found that using high-phase order of unique phasors further improves the performance. The iron losses are reduced, and the rippling behavior is lowered due to the smoother airgap magnetic flux density. Furthermore, a higher least-common-multiple (LCM) is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The efficiency remains constant even at low loads, which is particularly important for ship propulsion, as ships employ around 30% of the maximum power at cruise speed. Additionally, the use of superconductors provides the potential to reduce the weight and volume of the motor, which can have a significant impact on the overall weight and size of the propulsion system; • Wind turbines: Superconducting generators could increase the power output of wind turbines [8], especially offshore ones, by reducing the size and weight of the generator and increasing the efficiency [9]. In the year 2019, by the EU H2020 EcoSwing project [9], the world's first rotor for a 3.6 MW wind generator was successfully tested.…”
Section: Applications Of Superconducting Electric Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency remains constant even at low loads, which is particularly important for ship propulsion, as ships employ around 30% of the maximum power at cruise speed. Additionally, the use of superconductors provides the potential to reduce the weight and volume of the motor, which can have a significant impact on the overall weight and size of the propulsion system; • Wind turbines: Superconducting generators could increase the power output of wind turbines [8], especially offshore ones, by reducing the size and weight of the generator and increasing the efficiency [9]. In the year 2019, by the EU H2020 EcoSwing project [9], the world's first rotor for a 3.6 MW wind generator was successfully tested.…”
Section: Applications Of Superconducting Electric Machinesmentioning
confidence: 99%
“…Superconducting synchronous machines (SCSMs): These are synchronous machines that use superconducting windings in their rotor or stator. They can be used as generators [8] or motors [17], and provide high power density, high efficiency, and high power factor. Studies have shown that SCSMs can achieve efficiency levels of 99% at full load [7], compared to conventional motors that typically operate at around 94-96% efficiency;…”
Section: Types Of Superconducting Machinesmentioning
confidence: 99%